Literature Review Determination Productivity and Performance: DisciplineWork and Organizational Culture - Kadir, Irma; Ali, Hapzi; Harsasi, Meirani (International Journal of Advanced Multidisciplinary, 2023)
Work productivity and employee performance can run optimally and are directed influenced by various factors, including work discipline and organizational culture. These two factors will certainly influence the behavior of employees in government agencies to achieve goals. The purpose of this study was to determine whether work discipline and organizational culture affect work productivity and employee performance. This research was conducted on employees of the Maluku Province Governor's Office with a population of 567 people. The sample used was 235 respondents. The independent variables in this study are work discipline and organizational culture, while the dependent variable is work productivity and employee performance. Variable measurements were carried out using a Likert scale. Data analysis was performed using the SEM method with PLS.